ASUHAN KEBIDANAN KOMPREHENSIF PADA NY N USIA 25 TAHUN DI BPM TUGIRAH A.Md.Keb KEBUMEN - Ilmawati, Dinia; Kusumaningsih, Tri Puspa (Lembaga Riset Pengabdian Masyarakat dan Publikasi Ilmiah Institut Teknologi Bhakti Putra Bangsa Indonesia, 2023)
Health problems in Indonesia are mainly caused by high maternal and infant mortality rates. To improve quality health, the authors contribute by providing comprehensive midwifery care for pregnancy, childbirth, postpartum, newborn and family planning. The purpose of this case study is to provide and implement comprehensive midwifery care during pregnancy, childbirth, postpartum, newborn and family planning. The case study method used is descriptive observation at BPM Tugirah from September 2021 to April 2022. Providing comprehensive care to Mrs. N 25 years old G2 P1 A0 with normal pregnancy. Data collection was carried out through interviews, observation, examination and documentation. Data analysis using Varney's 7 steps approach. In this case study, the author has implemented and provided comprehensive midwifery care starting from pregnancy, childbirth, postpartum, newborns, neonates and family planning. From pregnancy to family planning there are no complications or complications. In this case study there is a gap between theory and practice, namely not using 60-step APN, in standard ANC examinations not using 14 T care and in theory the time required for cervical dilatation should be 60 minutes but in this case only 30 minutes. It is expected that patients are able to carry out early detection of high risk and the authors apply midwifery science in a comprehensive manner according to the theory and standards of the midwifery profession Keywords: Pregnancy, Childbirth, Postpartum, BBL, KB.